Colloquial Japanese the complete course for beginners - Clarke, H. D. B.; Hamamura, Motoko (London : Routledge, 2002)
Colloquial Japanese is easy to use and completely up to date. Specially written by experienced teachers for self study and class use, the course offers you a step-by-step approach to spoken and written Japanese. No previous knowledge of the language is required.
Keywords: Japanese language -- Conversation and phrase books; Japanese language -- Study and teaching; Japanese language -- Study and teaching -- Foreign speakers